Evaluating the mechanical properties of anisotropic shale containing bedding and natural fractures with discrete element modeling - Li, Yingjie; Song, Lihong; Tang, Yuanjun; Zuo, Jianping; Xue, Dongjie (International journal of coal science & technology, 2022)
Natural fracture data from one of the Carboniferous shale masses in the eastern Qaidam Basin were used to establish a stochastic model of a discrete fracture network and to perform discrete element simulation research on the size effect and mechanical parameters of shale. Analytical solutions of fictitious joints in transversely isotropic media were derived, which made it possible for the proposed numerical model to simulate the bedding and natural fractures in shale masses. The results indicate that there are two main factors influencing the representative elementary volume (REV) size of a shale mass. The first and most decisive factor is the presence of natural fractures in the block itself. The second is the anisotropy ratio: the greater the anisotropy is, the larger the REV. The bedding angle has little influence on the REV size, whereas it has a certain influence on the mechanical parameters of the rock mass. When the bedding angle approaches the average orientation of the natural fractures, the mechanical parameters of the shale blocks decrease greatly. The REV representing the mechanical properties of the Carboniferous shale masses in the eastern Qaidam Basin were comprehensively identified by considering the influence of bedding and natural fractures. When the numerical model size is larger than the REV, the fractured rock mass discontinuities can be transformed into equivalent continuities, which provides a method for simulating shale with natural fractures and bedding to analyze the stability of a borehole wall in shale.